Note from the Editor - Hopper, Madeline K. (Columbia Journal of Gender and Law, 2018)
The Columbia Journal of Gender and Law was honored to cosponsor the third annual conference of Empowering Women of Color at Columbia Law School (EWOC) entitled Double-Consciousness: Women of Color as Advocates for Ourselves and Others in March 2017.